2013
DOI: 10.1111/bij.12128
|View full text |Cite
|
Sign up to set email alerts
|

Female sika deer have evolved larger incisors than males under relaxed selection against rapid tooth wear

Abstract: Incisor size is associated with feeding efficiency in herbivorous ungulates and may have been under selection in correspondence with food habits. In the meantime, males of polygynous, dimorphic species have smaller cheek teeth than females, possibly because their reproductive span is much shorter than that of females. Thus, males are not under selection for more durable teeth when there is no reproductive return. Therefore, incisor size is expected to be under natural selection against wear and under the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Our results also showed that the factor ‘location’ made the greatest contribution of the random effects on molar and incisor wear, indicating that conditions prevailing at each particular area (e.g. hunting estates) can play an important role in tooth wear, in agreement with previous interpopulation comparisons [ 18 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results also showed that the factor ‘location’ made the greatest contribution of the random effects on molar and incisor wear, indicating that conditions prevailing at each particular area (e.g. hunting estates) can play an important role in tooth wear, in agreement with previous interpopulation comparisons [ 18 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Kubo et al [ 38 ] studied two sika deer ( Cervus nippon ) populations and only found heavier incisor wear in males in comparison with females in the population with stronger wear. These results suggest that although sexual selection may ultimately be responsible for male and female differences in tooth wear, environmental conditions may act to modulate them as has been shown for many other sexually dimorphic traits (see Bondurianski [ 40 ] and references herein).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of another sika deer population (Kinkazan Island population) under density‐dependent food limitation, Kubo et al . () found that tooth wear rate was significantly different between sexes. The presence or absence of sex differences in wear rate seems to be associated with the existence of sex differences in food habits.…”
Section: Discussionmentioning
confidence: 95%
“…In sexually dimorphic ruminants, energetic requirements and food selection are different between sexes (Mysterud, ), which in turn seems to be associated with faster molar wear rate in males than females (red deer: Loe et al ., ; Carranza et al ., ; but see Pérez‐Barbería et al ., for less a conspicuous sex difference in molar wear rate). Incisor wear of sika deer has shown similar patterns where males have faster wear rates than females in a population under density‐dependent resource limitation (Kubo et al ., ). It is interesting that, in both of molars and incisors, males of dimorphic species had relatively small teeth compared with females, though they had faster tooth wear rates (Carranza et al ., ; Carranza & Pérez‐Barbería, ; Kubo et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation